2018
DOI: 10.1038/s41598-018-26167-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of different surface modified carbon dots in pumpkin seedlings

Abstract: The distribution of surface modified carbon dots (CDs) in the pumpkin seedlings was studied by visualization techniques and their potential phytotoxicity was investigated at both the physiological and biochemical levels. The average size of carbon dots was approximately 4 nm. The fluorescent peaks of bared CDs, CD-PEI and CD-PAA were between 420 nm and 500 nm, indicating CDs could emit blue and green fluorescence. Fluorescent images showed that all three types of CDs could accumulate in the pumpkin roots and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…In another study, V. radiata sprouts were cultivated in the presence of N-doped C-dots (N-CDs) and a significant enhancement in the sprouts’ yield was observed compared to the aqueous control [ 81 ], indicating the effectiveness of N-CDs as a nitrogen nanofertilizer. Qian et al [ 82 ] compared the in planta distribution and the effects of three types of CDs (bared CDs, CD-PEI (modified by polyethylenimine), and CD-PAA (modified by polyacrylic acid)] on growth of C. pepo seedlings. It was found that all three types of CDs triggered the antioxidant defense systems (SOD, POD, CAT) [ 82 ].…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, V. radiata sprouts were cultivated in the presence of N-doped C-dots (N-CDs) and a significant enhancement in the sprouts’ yield was observed compared to the aqueous control [ 81 ], indicating the effectiveness of N-CDs as a nitrogen nanofertilizer. Qian et al [ 82 ] compared the in planta distribution and the effects of three types of CDs (bared CDs, CD-PEI (modified by polyethylenimine), and CD-PAA (modified by polyacrylic acid)] on growth of C. pepo seedlings. It was found that all three types of CDs triggered the antioxidant defense systems (SOD, POD, CAT) [ 82 ].…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…Qian et al [ 82 ] compared the in planta distribution and the effects of three types of CDs (bared CDs, CD-PEI (modified by polyethylenimine), and CD-PAA (modified by polyacrylic acid)] on growth of C. pepo seedlings. It was found that all three types of CDs triggered the antioxidant defense systems (SOD, POD, CAT) [ 82 ]. The available literature has recently been reviewed by [ 83 ].…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…A similar upward transport of CDs from the root of mung beans to the stem and leaves was reported by Kang et al 26,36 It should be noted that the distribution pattern of CDs in plants depends on their surface modification. 38…”
Section: Uptake Translocation and Accumulation Of Cds In Plantsmentioning
confidence: 99%
“…It is of particular interest to note that CQDs, as a consequence of their innately high hydrophilicity and high cell permeability, have frequently come to be used in water-based and biologically relevant applications [12,19].…”
Section: Cqds In Plantsmentioning
confidence: 99%